Antialgal activity of poly(2-(dimethylamino)ethyl methacrylate) (PDMAEMA) brushes against the marine alga Ulva. Issue 2 (7th February 2017) - Yandi, Wetra; Mieszkin, Sophie; Callow, Maureen E.; Callow, James A.; Finlay, John A.; Liedberg, Bo; Ederth, Thomas
Abstract: Marine biofouling has detrimental effects on the environment and economy, and current antifouling coatings research is aimed at environmentally benign, non-toxic materials. The possibility of using contact-active coatings is explored, by considering the antialgal activity of cationic poly(2-(dimethylamino)ethyl methacrylate) (PDMAEMA) brushes. The antialgal activity was investigated via zoospore settlement and sporeling growth assays of the marine algae Ulva linza and U. lactuca . The assay results for PDMAEMA brushes were compared to those for anionic and neutral surfaces. It was found that only PDMAEMA could disrupt zoospores that come into contact with it, and that it also inhibits the subsequent growth of normally settled spores. Based on the spore membrane properties, and characterization of the PDMAEMA brushes over a wide pH range, it is hypothesized that the algicidal mechanisms are similar to the bactericidal mechanisms of cationic polymers, and that further development could lead to successful contact-active antialgal coatings.